The Muknal cave near Tulum, Mexico: an early-Holocene funeral site on the Yucatán peninsula - Stinnesbeck, Sarah; Stinnesbeck, Wolfgang; Zell, Patrick; Frey, Eberhard; Lindauer, Susanne (The Holocene, 2018)
Here, we report on an incomplete human skeleton, soot patches related to anthropogenic fireplaces, and cut marks on the mandible of an extinct peccary, from the submerged Muknal cave southwest of Tulum on the Mexican Yucatán peninsula. The human individual, here named ‘Muknal Grandfather’, was identified as a male based on cranial parameters. The age at the time of death was estimated to be between 40 and 45 years. We propose that the human bones have been brought to the cave during the latest Pleistocene or early Holocene, but not later than 8600 14C yr BP (ca. 9600 cal BP), as a secondary burial of a partial skeleton. The peccary mandible was placed close to the burial site, possibly as part of the same ritual. The Muknal cave therefore served as a place for funeral rituals.
Gesehen am 17.04.2020